Dilema Loyalitas Dan Formalitas Dalam Keanggotaan Wajib Koperasi - Pramita Kusumawardhani; Florentina Anif Farida (PT. Intelek Cendikiawan Nusantara, 2026)
Cooperatives as a pillar of Indonesia's people-centered economy face a serious challenge when membership is mandatory, as members join not out of voluntary awareness but due to institutional policy. This condition creates a dilemma between loyality and formality, where members fulfill their obligations but do not necessarily develop a strong sense of belonging and engagement with the organization. This study aims to analyze the dilemma of loyalty and formality in the mandatory membership system of Koperasi Pegawai Republik Indonesia (KPRI) SMKN X Madiun, particularly in terms of member participation, internal marketing strategies, and challenges in member and management regeneration. A qualitative approach with a descriptive method was employed. Data were collected through direct interviews with a compulsory savings contribution and active participation. Members tend to participate due to institutional obligations rather than a genuine sense of ownership and commitment to the cooperative. In addition, the cooperative's services are perceived as less competitive than those offered by other financial institutions, resulting in low utilization of cooperative services. The cooperative is also interested in taking managerial roles. Therefore, service simplification, service quality improvement, and the development of a more participatory organization are due to members' low interest in taking managerial roles. Therefore, simplification, service quality improvement, and the development of a more participatory organizational culture are needed to strengthen member loyality and ensure organizational sustainability.